Feminist theatre practice : a handbook - Aston, Elaine (Routledge, 1999)
"Feminist Theatre Practice is a practical guide to theatre-making that explores the different ways of representing or 'seeing' gender. Designed to take the reader through the various stages of making feminist theatre - from warming up, through workshopped exploration, to performance - this volume is organised into three clear and instructive parts: women in the workshop; dramatic texts, feminist contexts; and gender and devising projects." "Orientated around the classroom/workshop, Feminist Theatre Practice encompasses the main elements of feminist theatre, whether practical or theoretical."--BOOK JACKET.